Landscapes after Dogme 95: Transnational Ambitions of Nordic Cinema and Television - Konefał, Jakub Sebastian (Uniwersytet Gdański, 2017)
The article focuses on the main artistic and economic strategies in the Nordic cinema and television in the last decade. The author analyses transnational turn on the Scandinavian movie market and describes the most important fields of academic researches connected with the Idea of North, Arctic studies and new wave of genre films from Norway, Iceland, and Finland. The last part of the text also discusses the order and subjects of the articles presented in the Nordic issue of "Panoptikum". The article focuses on the main artistic and economic strategies in the Nordic cinema and television in the last decade. The author analyses transnational turn on the Scandinavian movie market and describes the most important fields of academic researches connected with the Idea of North, Arctic studies and new wave of genre films from Norway, Iceland, and Finland. The last part of the text also discusses the order and subjects of the articles presented in the Nordic issue of "Panoptikum".